Plant isoquinoline alkaloids as potential neurodrugs: A comparative study of the effects of benzo[c]phenanthridine and berberine-based compounds on β-amyloid aggregation. (25th January 2021) - Marasco, Daniela; Vicidomini, Caterina; Krupa, Pawel; Cioffi, Federica; Huy, Pham Dinh Quoc; Li, Mai Suan; Florio, Daniele; Broersen, Kerensa; De Pandis, Maria Francesca; Roviello, Giovanni N.
Abstract: Herein we present a comparative study of the effects of isoquinoline alkaloids belonging to benzo[ c ]phenanthridine and berberine families on β-amyloid aggregation. Results obtained using a Thioflavine T (ThT) fluorescence assay and circular dichroism (CD) spectroscopy suggested that the benzo[ c ]phenanthridine nucleus, present in both sanguinarine and chelerythrine molecules, was directly involved in an inhibitory effect of Aβ1–42 aggregation. Conversely, coralyne, that contains the isomeric berberine nucleus, significantly increased propensity for Aβ1–42 to aggregate. Surface Plasmon Resonance (SPR) experiments provided quantitative estimation of these interactions: coralyne bound to Aβ1–42 with an affinity (KD  = 11.6 μM) higher than benzo[ c ]phenanthridines. Molecular docking studies confirmed that all three compounds are able to recognize Aβ1–42 in different aggregation forms suggesting their effective capacity to modulate the Aβ1–42 self-recognition mechanism. Molecular dynamics simulations indicated that coralyne increased the β-content of Aβ1–42, in early stages of aggregation, consistent with fluorescence-based promotion of the Aβ1–42 self-recognition mechanism by this alkaloid. At the same time, sanguinarine induced Aβ1–42 helical conformation corroborating its ability to delay aggregation as experimentally proved in vitro . The investigated compounds were shown to interfere with aggregation of Aβ1–42 demonstrating their potential as starting leads for the development of therapeutic strategies in neurodegenerative diseases. Graphical abstract: Image 1 Highlights: We compared the effects of three isoquinoline alkaloids on β-amyloid aggregation. Sanguinarine and chelerythrine showed inhibitory effects on Aβ1–42 aggregation. Coralyne significantly increased propensity for Aβ1–42 to aggregate. Molecular dynamics suggested the alkaloid ability to affect β-content of Aβ1–42 .